2012
DOI: 10.1088/0022-3727/45/29/293001
|View full text |Cite
|
Sign up to set email alerts
|

Laser-assisted water condensation in the atmosphere: a step towards modulating precipitation?

Abstract: We review the recent results about laser-induced condensation based on self-guided filaments generated by ultrashort laser pulses. After recalling the physico-chemistry of cloud particle formation in the atmosphere and the physics of laser filamentation, we discuss experimental results on laser-induced condensation and its relevance for modulating precipitations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 110 publications
(140 reference statements)
0
11
0
Order By: Relevance
“…There will be attenuation of energy in this propagation. Kasparian et al [10] experimented with terawatt laser from the ground and observed tiny raindrops in an altitude of 45 to 75m of the atmosphere. To create large water droplets at higher altitudes, the group feels that laser power has to be peta-watt (10 15 watt) or hexa-watt (10 18 watt).…”
Section: Theory and Methodologymentioning
confidence: 99%
“…There will be attenuation of energy in this propagation. Kasparian et al [10] experimented with terawatt laser from the ground and observed tiny raindrops in an altitude of 45 to 75m of the atmosphere. To create large water droplets at higher altitudes, the group feels that laser power has to be peta-watt (10 15 watt) or hexa-watt (10 18 watt).…”
Section: Theory and Methodologymentioning
confidence: 99%
“…Furthermore, we propose to use this signal to extract physical or chemical parameters (T, RH, pre--existing nanoparticles, volatile organic compound (VOC) concentration…) that influence laser--induced condensation [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…In order to better characterize propagation at the sub-PW level, direct horizontal measurements over several hundred meters are required. The photon bath of high energy and high power laser beam can play an important role in practical applications such as laser promoted particle formation [42][43][44], and therefore, it deserves further investigation. It also has to be taken into account in analyzing Lidar signals based on the supercontinuum.…”
Section: Introductionmentioning
confidence: 99%